Occurrence of trace elements and their impact on human health around waste dumping sites - Richard P. Bature; Peter S. Hooda; David Kidd; Rosa Busquets; David M. Bwai (Environmental Geochemistry and Health, 2026)

Estimation of pKa values in membrane bound proteins - Jesse W. Jones; Nereu Montserrat i Busquets; Ana P. Gamiz-Hernandez; Ville R.I. Kaila; Maria A. Mroginski (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Environmental plastics in the context of UV radiation, climate change, and the Montreal Protocol - Marcel A. K. Jansen; Anthony L. Andrady; Paul W. Barnes; Rosa Busquets; Laura E. Revell; Janet F. Bornman; Pieter J. Aucamp; Alkiviadis F. Bais; Anastazia T. Banaszak; Germar H. Bernhard; Laura S. Bruckman; Donat‐P. Häder; et al. (Global Change Biology, 2024)

P22-23: Expediting the uptake of Next-Generation Risk Assessment (NGRA) into EU chemicals legislation under PARC - M. Herzler; I. Apruzzese; N. Bandow; F. Busquet; A. Cavoski; J. Colbourne; E. Di Consiglio; M. Dusinska; G. Flingelli; L. Holden; R. Hornek-Gausterer; A. Kaiser; et al. (Toxicology Letters, 2023)

The EU-ToxRisk method documentation, data processing and chemical testing pipeline for the regulatory use of new approach methods - Alice Krebs; Barbara M. A. van Vugt-Lussenburg; Tanja Waldmann; Wiebke Albrecht; Jan Boei; Bas ter Braak; Maja Brajnik; Thomas Braunbeck; Tim Brecklinghaus; Francois Busquet; Andras Dinnyes; Joh Dokler; et al. (Archives of Toxicology, 2020)
Hazard assessment, based on new approach methods (NAM), requires the use of batteries of assays, where individual tests may be contributed by different laboratories. A unified strategy for such collaborative testing is presented. It details all procedures required to allow test information to be usable for integrated hazard assessment, strategic project decisions and/or for regulatory purposes. The EU-ToxRisk project developed a strategy to provide regulatorily valid data, and exemplified this using a panel of > 20 assays (with > 50 individual endpoints), each exposed to 19 well-known test compounds (e.g. rotenone, colchicine, mercury, paracetamol, rifampicine, paraquat, taxol). Examples of strategy implementation are provided for all aspects required to ensure data validity: (i) documentation of test methods in a publicly accessible database; (ii) deposition of standard operating procedures (SOP) at the European Union DB-ALM repository; (iii) test readiness scoring accoding to defined criteria; (iv) disclosure of the pipeline for data processing; (v) link of uncertainty measures and metadata to the data; (vi) definition of test chemicals, their handling and their behavior in test media; (vii) specification of the test purpose and overall evaluation plans. Moreover, data generation was exemplified by providing results from 25 reporter assays. A complete evaluation of the entire test battery will be described elsewhere. A major learning from the retrospective analysis of this large testing project was the need for thorough definitions of the above strategy aspects, ideally in form of a study pre-registration, to allow adequate interpretation of the data and to ensure overall scientific/toxicological validity.

Survey of laboratory-acquired infections around the world in biosafety level 3 and 4 laboratories - N. Wurtz; A. Papa; M. Hukic; A. Di Caro; I. Leparc-Goffart; E. Leroy; M. P. Landini; Z. Sekeyova; J. S. Dumler; D. Bădescu; N. Busquets; A. Calistri; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The relationship between carbonate facies, volcanic rocks and plant remains in a late Palaeozoic lacustrine system (San Ignacio Fm, Frontal Cordillera, San Juan province, Argentina) - P. Busquets; I. Méndez-Bedia; G. Gallastegui; F. Colombo; R. Cardó; O. Limarino; N. Heredia; S. N. Césari (International Journal of Earth Sciences, 2013)